Clinical study on the correlation between radiological and intra operative findings in cases of sino nasal polyposis - Tiwari, Aishwarya; Varadharajan, Ramesh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Sino nasal polyposis is a common condition often encountered by the otolaryngologists. Though plain radiographs are valuable in the pre-operative evaluation, the CT scan plays a major role in identifying the extent of disease and the anatomic variations accurately for the surgeon. This study evaluates the value of pre-operative CT scans by correlating the scan findings with intra-operative surgical findings. Methods: Total 50 adult patients who attended the ENT department from November 2018 to October 2020 with Sino nasal polyposis were selected for the study. All were subjected to CT scan and underwent Functional Endoscopic Sinus Surgery. The intra-operative findings were compared with the CT scan findings. Results: In our study, the pre-operative CT scan showed single sinus involvement in 20% and multiple sinus involvement in 80% of cases. Mucosal abnormality was reported in 86% and normal in 14% of cases. Osteomeatal obstruction was reported in 44% and normal in 56% of cases. Various anatomical abnormalities were noted in 100% of cases. There was a perfect positive co relation between CT scan findings and intra operative findings with regards to Osteomeatal occlusion and anatomical or mucosal abnormalities. Conclusions: The study done to assess the correlation between pre-operative CT scan findings and intra-operative findings of Sino nasal polyposis cases has shown a perfect positive correlation between the findings. Pre-operative CT scan is an invaluable tool for the surgeon for accurate diagnosis and treatment planning.